(untitled) (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
It is very important to highlight the unique experience of transplanting the achievements of Oriental Buddhist culture to the Mongolian land and the unique features that it contributed to Mongolian cultural history from the works of the Lamyn gegeen Luvsandanzanjantsan, written in Tibetan, the scientific and religious language of his time, three centuries ago. At the same time, the study was conducted to demonstrate the validity of the WHO’s guidelines for evidence-based development of traditional medicine and to research the works of Mongolian doctors. To identify the medicines written with evidence by comparing the medical work of the Mongolian Lamyn gegeen Luvsandanzanjantsan, “Man ngag bdud rtsi zegs ma.” The study was conducted using the comparative method of source literature, the method of source literature classification, the method of analysis-synthesis, and the method of hermeneutics. There are 36 proven recipes in the work “Man ngag bdud rtsi zegs ma,” which is 24.2% of the total recipes in the work. These include: In addition to naming the recipes for treating diseases, it clearly states the additions, side effects, and which diseases are suitable for which diseases. It clearly states the method of preparing widely used recipes. It clearly states the method of preparing and administering medicines according to the stage of chronic and severe diseases, which is of high clinical significance. The recipes in this work are based on his many years of medical experience. The recipes for treating diseases are widely used, accounting for 7.4% of the total recipes in this work. Many secret recipes from Lamyn gegeen Luvsandanzanjantsan’s hand are included. It is unique that he used a combination of medicine and mantra to treat. The Lamyn gegeen Luvsandanzanjantsan systematically summarized his observations and experiences in this work, wrote about traditional medicines that had clear treatment results, and was the first to create evidence-based medical education in Mongolia.